Editorial IEEE TNSRE Has a New Editor-in-Chief!! - Daniel P. Ferris; He Huang (IEEE, 2023)
After six years of serving as the Editor-in-Chief (EiC) for IEEE Transactions on Neural Systems and Rehabilitation Engineering (TNSRE), I am ready to pass on the baton. It has been a fun job and I am very happy to have had the opportunity. However, the workload is increasing every year and it is time. Before I started in the role, there were 114 new manuscript submissions for 2017. This year (2023), we have received more than 1000 new manuscript submissions. In 2017, there were 27 associate editors (AEs) (25 males and two females) with 15 of them from North America. There are currently 71 AEs (38 males and 33 females) with 21 of them from North America. This increase in editorial board size and diversity is a major improvement from my perspective. I am also proud that our two-year journal impact factor increased from 3.3 in 2018, to 4.9 in 2022, while still maintaining a ~40% rejection rate. That impact factor ranks the journal 4th out of 68 journals in the rehabilitation category within Science Citation Index Expanded (SCIE). One of the major factors contributing to the rise in impact factor, in my opinion, was the successful flipping of the journal from hybrid open access to gold open access. Every paper we publish is freely available to everyone with an Internet connection around the world. An important part of that flip was the ability to keep the article processing charges (APC) low. The APC fee is currently U.S. ${\$}$ 1950 and we have mechanisms in place to reduce the APC for researchers from countries with historically lower economic status. The journal has come a long way since its beginnings.